COMPARATIVE ANALYSIS OF BAND LIGATION TECHNIQUE VERSUS CONVENTIONAL HEMORRHOIDECTOMY FOR THE TREATMENT OF GRADE III HEMORRHOIDS - MAHNA, ABHISHEK (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: A comparative study between band ligation technique and conventional hemorrhoidectomy for the treatment of Grade III hemorrhoids was carried out to compare operative and post-operative variables. Methods: This study was done on a sample size of 70 patients with Grade III hemorrhoids from 2019 to 2020 in the department of surgery of a medical college. Informed written consent was taken from the patients after explaining the benefits and side effects of both methods. The eligible patients were randomly divided into Group A (35 patients) for treatment by band ligation procedure and Group B (35 patients) who were treated by the conventional technique. The obtained data were subjected to statistical analysis by applying an unpaired t-test using SPSS 19.0 software. Results: The difference between the two groups of the average age was comparable. The operative time and intraoperative bleeding were significantly lower in Group A than in Group B. The time to first bowel movement (hr) and average hospital stay were significantly lower in Group A than in Group B. Furthermore, the average number of analgesic doses required was significantly lower in Group A than in Group B. Furthermore, the time required for wound healing was significantly lower in Group A. The overall complications were found to be quite less in Group A than in Group B. Conclusion: The rubber band ligation technique revealed better results in terms of operative and post-operative parameters as compared to the conventional hemorrhoidectomy.